Influence de la vitesse sur la détente verticale lors de l`exécution du smash en volleyball - Bouhedja, T.; Hamida, M. L.; Djemai, H. (Science & Sports, 2021)
Objective The aim of this research is to study the level and the degree of influence of speed as a determining biomechanical parameter to achieve the best performance of vertical jump in attacking volleyball players during the various stages of execution of the smash.